Comparative Direct Compression Property of a Novel Pregelatinized Starch in Paracetamol Tablets - Tamrat Balcha Balla; Nisha Mary Joseph; Anteneh Belete (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Among all the pharmaceutical dosage forms, tablets are still the most preferred and the most commonly used option because of their advantages. The direct compression method of tablet preparation exempts several steps needed in the granulation method. Therefore, the pursuit of better direct compression tablet excipients is evident in contemporary research endeavors. Pregelatinized Taro Boloso-I starch has comparable flow properties and higher compressibility and compactibility than Starch 1500®. However, there is no evidence in the literature regarding the lubricant sensitivity and dilution potential of pregelatinized Taro Boloso-I starch. This study was aimed at performing the in vitro evaluation of paracetamol tablets prepared using pregelatinized Taro Boloso-I starch as a direct compression excipient using paracetamol as a model drug. Methods. Taro Boloso-I starch was pregelatinized, and its properties including amylose to amylopectin ratio, densities, flow properties, swelling power, water solubility index, particle morphology, moisture content, and moisture sorption profile were evaluated. Furthermore, the lubricant sensitivity test, dilution potential study, and compatibility test with the paracetamol drug using ATR spectroscopy were performed. The properties of the directly compressed tablets prepared accordingly were evaluated. The majority of evaluations were performed in comparison with Starch 1500®. Results and Discussion. PGTBIS had a significantly lower amount of amylose than Starch 1500®. In the ATR-IR spectra of the mixture of the paracetamol and pregelatinized PGTBIS, all the major absorbance peaks of the drug were maintained indicating the absence of chemical modifications. PGTBIS showed better flow properties than Starch 1500®. The modified starch was shown to withstand magnesium stearate up to 0.5% concentration. Conclusion. PGTBIS could accommodate higher drug cargo than Starch 1500® with acceptable tablet properties. Accordingly, PGTBIS starch could be taken as a potential direct compression excipient.